EFFICACY ASSESSMENT OF THE RADIO-WAVE SURGERY AND THE HIGH-FREQUENCY ELECTROSURGERY IN THE TREATMENT OF PATIENTS WITH THE COMBINED ANAL CANAL AND RECTUM PATHOLOGY - Balytskyi, V.V.; Zakharash, M.P.; Kurik, O.H. (World of Medicine and Biology, 2019)
The surgical treatment results obtained in 236 patients with combined pathology of anal canal and rectum using “Surgitron” radio wave surgery device, as well as 50 patients with combined pathology of anal canal and rectum using “KLS Martin” high-frequency electrosurgical device have been analyzed. According to the study results, it was established that using “Surgitron” radio wave surgery device and “KLS Martin” high-frequency electrosurgical device reduces the operation length to 15±5 min, bleeding volume - to 20±10 ml, need of narcotic analgesics - to 2±1 ml and the period of inpatient treatment - to 4±1 days. The morphological study results indicate that application of the above modern technologies leads to insignificant depth of tissue necrosis from 0.165±0.11mm in case of using “Surgitron” device to 0.192±0.12мм in case of using “KLS Martin” device providing cosmesis of the operations.
Keywords: radio-wave surgery device; high-frequency electrosurgical device; metal surgical scalpel; combined pathology; anal canal; rectum